Gaining situation awareness through a vibrotactile display to mitigate motion sickness in fully-automated driving cars - Md. Yusof, Nidzamuddin; Karjanto, Juffrizal; Terken, Jacques M.B.; Delbressine, Frank L.M.; Rauterberg, G. W. Matthias (Universiti Malaysia Pahang, 2020)
Many previous studies mention that passive drivers or passengers of fully automated driving cars have less awareness of the surrounding and more experience to motion sickness symptoms when engaging in non-driving tasks. This occurrence is especially magnified when riding in an urban area with lots of junctions and corners. The aim of the current study is to investigate the effects of peripheral information about upcoming manoeuvres through a vibrotactile display in increasing the fully-automated driving car passengers’ awareness of situations and mitigating their motion sickness level. Twenty participants took part in the experiment which used a Wizard of Oz method to simulate autonomous driving, and the experiment was conducted in an instrumented car on a real road environment. Objective and subjective measurements were gathered. The results show that the implementation of the vibrotactile display increased situation awareness but failed to reduce the motion sickness. This study concludes that in order to mitigate motion sickness inside a fully-automated driving car, more specific information need to be included in the peripheral information. In addition, a device that can actively help in controlling the posture movements should also be implemented in the vehicle.